Epic disruptions : 11 innovations that shaped our modern world - Anthony, Scott D. (Harvard Business Review Press, 2025)
"From gunpowder to generative AI, the forces of disruption are repeatedly rewriting the rules of business, society, and human possibility. But what really drives these revolutionary changes? In Epic Disruptions, innovation expert Scott Anthony masterfully weaves together the fascinating stories behind history's most transformative disruptions-from ninth-century China to twenty-first-century Silicon Valley. Through eleven pivotal innovations, including the printing press, mass-produced automobiles, the McDonald's revolutionary food system, and the iPhone, Anthony reveals the hidden patterns behind world-changing breakthroughs. But Epic Disruptions goes beyond just celebrating invention. Through vivid storytelling and sharp analysis, Anthony introduces the iconoclasts who dared to think differently-the Renaissance-era scientists, French-cooking enthusiasts, and corporate visionaries who saw opportunities others missed. He decodes how genuine disruption actually happens, stripping away the mythology. As artificial intelligence and other technologies promise to unleash another wave of transformation, Epic Disruptions arrives at the perfect moment-offering innovators and curious readers a page-turning exploration of how radical change reshapes industries, launches new powers, and, yes, occasionally changes everything"-- Provided by publisher.